Multiple endothermic transitions of acid hydrolyzed and heat-moisture treated corn starch. (August 2017) - Xing, Jun-jie; Li, Dong; Wang, Li-jun; Adhikari, Benu
Abstract: The multiple thermal transitions of acid-hydrolyzed and heat-moisture treated corn starch samples in excess water were measured using differential scanning calorimetry (DSC) and interpreted using a polymer swelling and dissolution theory. The dual treatment of acid hydrolysis (AH) and heat-moisture treatment (HMT) with different extent of reaction generates starches with various degrees of residual crystalline structure. Multiple endothermic transitions (G and M1) were firstly observed in DSC traces even in excess water. In this study, the G and M1 endotherms were proposed to be related with the energy consumption associated with granule swelling and crystallites dissolution respectively. In contrast, only a single M1 endotherm transition from a broad to a sharp and narrow endotherm upon HMT was consistently observed for starch samples acid hydrolyzed for 48 and 72 h, which testified the dominance of rearrangement over the destruction upon HMT. This novel theory describing the multiple phase transition was also evidenced by the variation of swelling power and relative crystallinity. Highlights: Biphasic endotherms were both observed in DSC traces even in excess water. Thermal transitions were interpreted well by starch swelling and dissolution theory. The first endotherm was associated with the swelling of partially degraded starches. The second endotherm was related to the dissolution of residual crystalline starch. Heat-moisture treatment increased swelling power of prolonged hydrolyzed starch.